Enhanced decision making and working memory during exercise in the heat with crushed ice ingestion - Saldaris, J. M.; Landers, G. J.; Lay, B. S. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the effects of precooling via crushed ice ingestion on cognitive function during exercise in the heat. Methods: Eleven active men ingested either 7 g·kg-1 of crushed ice (ICE) or thermoneutral water (CON) 30 minutes before running 90 minutes on a treadmill at a velocity equivalent to 65% VO2peak in hot and humid conditions (35.0°C [0.5°C], 53.1% [3.9%] relative humidity). Participants completed 3 cognitive tasks to investigate decision making (8-choice reaction time [CRT]), working memory (serial seven [S7]), and executive control (color multisource interference task [cMSIT]) on arrival, after precooling, and after running. Results: Precooling significantly decreased preexercise core (Tcore) and forehead skin temperature in ICE compared with CON, respectively (Tcore 0.8°C [0.4°C], -0.2°C [0.1°C]; Thead -0.5°C [0.4°C], 0.2°C [0.8°C]; P=.05). Postrun, ICE significantly reduced errors compared with CON for CRT (P=.05; d=0.90; 90% confidence interval, 0.13-1.60) and S7 (P=.05; d=1.05; 90% confidence interval, 0.26-1.75). Thermal sensation was lower after precooling with ICE (P=.05), but no significant differences were recorded between conditions for cMSIT errors, skin temperature, heart rate, or ratings of perceived exertion or perceived thirst (P>.05). Conclusions: Precooling via ICE maintained cognitive accuracy in decision making and working memory during exercise in the heat. Thus, ICE may have the potential to improve sporting performance by resisting deleterious effects of exercise in a hot and humid environment on cognitive function.